KONFIGURASI DAN KOMPOSISI SEBAGAI PENDEKATAN DALAM GUBAHAN BENTUK ARSITEKTUR - Wahyudi Siswanto (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2012)
The rules of configuration and composition have been known for so long in the history of architecture. Both are methods and design approaches that are connected one to another, nevertheless in many cases, they were seen as opposition one to another, along with the change views and concepts that are applied by scientists and designers. By understanding the meaning, function and the development of configuration and composition in architectural design, the critical scientific standpoint toward both ofÂ the methods can be achieved. Keywords: Configuration, Compotition, Design methode.